Development of a two-stage biotransformation system for mercury-contaminated soil remediation. (June 2018) - Chen, S.C.; Lin, W.H.; Chien, C.C.; Tsang, D.C.W.; Kao, C.M.
Abstract: Utilization of bacterial volatilization can be problematic to remediate mercury (Hg)-contaminated soils because most of the Hg in soils is bound to soil particles. The objective of this study was to develop a two-stage system (chemical extraction followed by microbial reduction) for Hg-contaminated soil remediation. The tasks were to (1) select the extraction reagents for Hg extraction, (2) assess the effects of extraction reagents on the growth of Hg-reducing bacterial strains, and (3) evaluate the effectiveness of Ca 2+ and Mg 2+ addition on merA gene (Hg reductase) induction. Bacterial inhibition was observed with the addition of 0.1 M ethylenediaminetetraacetic acid or citric acid. Up to 65% of Hg was biotransformed (Hg concentration = 69 mg/kg) from the soils after a 24 h extraction using 0.5 M ammonium thiosulfate. Ca 2+ and Mg 2+ were selected because they have the same electric charge as Hg and the studied groundwater contained high concentrations of Ca 2+ and Mg 2+ . Results showed that the addition of 200 mg/L Ca 2+ or 650 mg/L Mg 2+ could reach effective merA induction. In the two-stage experiment, 120 mg/kg Hg-contaminated soils were extracted with 2 rounds of extraction processes for 10 h using 0.5 M ammonium thiosulfate. Approximately 77% of Hg was extracted from the soils after the first-step extraction process. Up to 81% of Hg 2+ was transformed from the washing solution via the biotransformation processes with Enterobacter cloacae addition and Ca 2+ and Mg 2+ supplementation. The two-stage remedial system has the potential to be developed into a practical technology to remediate Hg-contaminated sites. Highlights: A two-stage (chemical and microbial) system can be used to treat Hg-polluted soils. B7 strain ( Enterobacter cloacae ) had effective Hg bioreduction efficiency. Addition of Ca 2+ and Mg 2+ induced merA gene effectively. Thiosulfate had less growth inhibition to Hg-reducing bacteria.